Quality of prescribing in patients with hypertension: A narrative review - Santoso, Devina Erawati; Wibowo, Yosi Irawati; Setiadi, Adji Prayitno (Jurnal Ilmiah Medicamento, 2024)
Assessing the rational use of medicines or prescription quality is essential in any health system. However, data on the quality of prescribing in patients with hypertension is currently lacking. Hence, this review aimed to identify prescribing quality indicators in patients with hypertension and understand the results. A narrative review was conducted to include literature searching in three databases, including PubMed (Medline), Science Direct, and CINAHL, using keywords and Boolean Logic as follows: “(hypertension OR antihypertensive drugs OR antihypertensive medication OR antihypertensive agent) AND (quality prescription OR inappropriate prescribing OR potentially inappropriate medication OR rational prescribing)”. As a result, a total of 1889 articles were obtained. The articles were then selected based on inclusion and exclusion criteria in which 13 articles were included in this review. Based on the extracted data, explicit as well as implicit frameworks have been used to assess the quality of prescribing in patients with hypertension. Explicit approaches compared patient prescription versus guidelines (n=7 articles) or lists of potentially inappropriate use of medicines (n=3 articles). The implicit framework assessed patient prescription using two tools, including the prescription Quality Index (PQI) – 22 indicators (n=2 articles), and the prescription quality checklist – four indicators (n=1 article). The results of the quality assessment on the prescriptions showed that prescriptions categorized as good quality were between 40-80%. While varied levels of inappropriate selection of antihypertensive therapy were reported (0-65%). In addition, more than 30% of patients with hypertension experienced Potentially Inappropriate Medication (PIM); thus, prescribing among patients with hypertension needs to be optimized.